Yi Ik: Korean Practical Philosopher and Moralist of the Late Joseon Period - Yuri Smertin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The article analyzes the ideological and theoretical views of the Korean intellectual, scholar Yi Ik (1681–1763), on modern society and his proposed measures for its improvement. Yi Ik was one of the main pillars of the Sirhak intellectual movement, which became the basis for the profound transformation of Korean society in the 19th century. Methods and materials. The research was carried out on the basis of a civilizational approach to the study of history, proceeding from the specifics of cultural and historical societies (in this case, the so-called Confucian civilization covering the countries of East Asia) and the anthropological approach, which considers men as products of their epoch. The main source was Yi Ik’s “Songho saseol,” (“Miscellaneous Sayings of Songho”). Analysis. This work is a collection of thoughts, facts, and commentaries recorded by the author over the course of several decades. It is encyclopedic in nature and includes information on history, military affairs, philosophy, mathematics, astronomy, geography, medicine, agriculture, literature, and music. He was especially interested in the reorganization of Korean society on the basis of humanity and justice. This work was written in Wenyang (kor. Hanmun), the literary Chinese language that was the official script in medieval Korea. “Songho saseol” published in 1970 by Munhwasa publishers in Seoul, is used in this article. The pages are offset photographs and are not numbered. Results. The main focus of Yi Ik’s writings was agriculture, the backbone of Korea’s economy. His economic ideas, which were based on Confucian tenets, were largely idealistic. Other ideas concerning social reforms and the adoption of Western science and technology were in line with the demands of the times and later became the basis for the transformation of Korean society. The main conclusion is that in his scientific and practical work, Yi Ik sought to synthesize the humanitarian Confucian thought and practical knowledge from Western sources.